The Next Generation of Immersive Surgical Education: We Must Achieve Presence - Schoenecker, Jonathan G.; Tummins, Madi Shultz; Moore-Lotridge, Stephanie N. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
There is a need for providing cost-efficient simulation of pediatric orthopaedic pathology that permits training with unlimited repetitions and no possibility of harming a child. New generation virtual reality simulation has potential in surgical training to accomplish this goal. While the technology has drastically improved, there remain significant challenges to rolling out VR as an educational tool, particularly for the more experienced learner. In this article, the authors provide barriers and potential solutions to these challenges.